Electrical & electronic engineering : theory and application series 2 : embedded system, mechatronic and image processing - Mohd. Muji, Siti Zarina (Penerbit UTHM, 2015)
This book is a collection of ultrasonic project for Microcontroller and Microprocessor subject did by third year students in Faculty of Electric and Electronic Engineering, (UTHM). This book chapter is very useful for the reader to understand the ultrasonic operation and how to program the sensor using PIC microcontroller. It is hope that this book can help the reader to build the application based ultrasonic sensor that can be used for their daily live.